Circulating Activin A predicts survival in cancer patients. Issue 5 (15th July 2017) - Loumaye, Audrey; de Barsy, Marie; Nachit, Maxime; Lause, Pascale; van Maanen, Aline; Trefois, Pierre; Gruson, Damien; Thissen, Jean‐Paul
Abstract: Background: Several experimental evidences pinpoint the possible role of Activin A (ActA) as a driver of cancer cachexia. Supporting this hypothesis, we showed recently that human cancer cachexia is associated with high ActA levels. Moreover, ActA levels were correlated with body weight loss and skeletal muscle density, two prognostic factors in cancer patients. Our goal was therefore to investigate the value of ActA to predict survival in cancer patients. Methods: Patients with colorectal or lung cancer were prospectively enrolled at the time of diagnosis or relapse between January 2012 and March 2014. At baseline, patients had clinical, nutritional, and functional assessment. Body composition and skeletal muscle density were measured by CT scan, and plasma ActA concentrations were determined. Overall survival (OS) was analysed since inclusion to 24 months later. Results: Survival data were available for 149 patients out of 152. Patients with high ActA (≥408 pg/mL) had lower OS than those with low levels, regardless the type of cancer (OS in colorectal cancer, 50% vs. 79%, P < 0.05; and in lung cancer, 27% vs. 67%, P = 0.001). The multivariable analysis confirmed the prognostic value of ActA independently of tumour stage or inflammatory markers, particularly in lung cancer. Low muscularity was also an independent prognostic factor. Conclusions: Our study demonstrates that high ActA level is an independent prognosis factor of survival in cancer patients. More than a basic marker of the severity of the neoplastic disease or of the inflammatory process, ActA seems to influence survival by contributing to the development of cachexia and loss of skeletal muscle mass.